Probable use of regional situational centers of the intellectual system «Сontrol_TEE» using UAVs - Pisarenko, J.V.; Melkumyan, E.Yu.; Koval, A.S. (Інститут програмних систем НАН України, 2023)
To ensure the optimal functioning of the complex objects of new technology and information systems being created, it is important to develop the principles of building hardware complexes taking into account the specifics of the cycle of a techno-ecological events. In this work, attention is paid to the further development of the methodological approach to the creation of a situational center based on a model of a geo-information sys- tem using a technopark of robotic systems with elements of AI, which implements a software complex of communication of unmanned transport of general purpose in the city environment with the base, helps to reduce costs and during crisis situations in which the access of expert people is difficult or fundamentally impossible. The charter of the sports federation of unmanned aviation of the sports and engineering direction has been developed, which unites athletes, coaches, sports judges, specialists and amateurs of organizations interested in the development of the sport of unmanned aviation and aerobatics shows. A multi-level architecture scheme for building a network of regional situational centers has been developed. Information about the UAVs movement in the city is sent to the central situational center (CSC) from the regional ones, all requests for UAVs to perform certain actions are sent to it via the Internet, this information is processed and decisions are made here, and all necessary communications are deployed here services regional situational centers, located in the protected perimeter, conduct radio exchange with UAVs in their area of operation, manage their area according to the general plan dictated by the CSC, have functionality for autonomous traffic control and execution of requests in case of loss communication with the CSC.Prombles in programming 2022; 3-4: 349-354